Utilization of Instagram as An Instrument of Public Policy Transparency: A Case Study of The Palangka Raya City Government - Refa Asmianur; Taufiqurokhman Taufiqurokhman; Evi Satispi; Andriansyah Andriansyah; Akwila T.A Awan (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
The rapid development of digital communication has encouraged local governments to use social media to strengthen public policy transparency. Instagram, as a visually oriented and interactive platform, is increasingly adopted to disseminate policy information and public service messages. This study examines how the Palangka Raya City Government uses Instagram to support public policy transparency by focusing on: (1) the types of policy information communicated and their framing, (2) the dominant communication strategy pattern (push, pull, or networked), and (3) the implications of these practices for citizen interaction and perceived transparency. The study adopts a purposive case approach and qualitative content analysis. Data were drawn from peer-reviewed academic literature, official local government documents, publicly accessible Instagram content from relevant official accounts, and supporting news coverage (2019–2024). The analysis assessed informational completeness (why–what–how–so what), communication strategies, and observable interaction cues (e.g., questions, complaints, clarifications, and visible responses). The findings indicate that Instagram contributes to transparency mainly by increasing policy visibility and providing basic informational access. Substantive transparency is more evident in service-oriented posts that offer actionable guidance and link citizens to formal disclosure and complaint mechanisms such as KIP/PPID and SP4N-LAPOR. However, communication remains predominantly push-oriented, while pull-based interaction is limited and networked collaboration is largely absent. Consequently, digital transparency tends to emphasize information dissemination rather than demonstrably meaningful participation, and any implications for public trust are discussed as inferences rather than directly measured outcomes.